Study Of the Pattern And Trend Of Venture Capital Financing In India Since Liberalization - Somani, Samridhi (2008)
It basically refers to the study of venture capital financing in India,its pattern since 1986 till present in the thesis data has been collected till present.Detailed study has been conducted in order to observe the changes in venture capital regulation,pattern and comparision between private and public sector firms etc.